Altering Opioid Neuromodulation in the Songbird Basal Ganglia Modulates Vocalizations - Kumar, Sandeep; Mohapatra, Alok Nath; Sharma, Hanuman Prasad; Singh, Utkarsha A.; Kambi, Niranjan Ashok; Velpandian, Thirumurthy; Rajan, Raghav; Iyengar, Soumya (Frontiers in Neuroscience, 2019)
Although the interplay between endogenous opioids and dopamine (DA) in the basal ganglia (BG) is known to underlie diverse motor functions, few studies exist on their role in modulating speech and vocalization. Vocal impairment is a common symptom of Parkinson’s disease (PD), wherein DA depletion affects striosomes rich in μ-opioid receptors (μ-ORs). Symptoms of opioid addiction also include deficiencies in verbal functions and speech. To understand the interplay between the opioid system and BG in vocalization, we used adult male songbirds wherein high levels of μ-ORs are expressed in Area X, a BG region which is part of a circuit similar to the mammalian thalamocortical-basal ganglia circuitry. Changes in DA, glutamate and GABA levels were analysed during the infusion of different doses of the μ-OR antagonist naloxone (50 and 100ng/ml) specifically in Area X. Blocking μ-ORs in Area X with 100ng/ml naloxone led to increased levels of DA in this region without altering the number of songs directed towards females (FD). Interestingly, this manipulation also led to changes in the spectro-temporal properties of FD songs, suggesting that altered opioid modulation in the thalamocortical-basal ganglia circuit can affect vocalization. Our study suggests that songbirds are excellent model systems to explore how the interplay between μ-ORs and DA modulation in the BG effects speech/vocalization.